Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1134/s1063774512040098
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarities of quasi-longitudinal elastic wave propagation through the interface between isotropic and anisotropic media: Theoretical and experimental study

Abstract: The peculiarities of elastic wave propagation in a bilayer medium are studied theoretically and experimentally. One (isotropic) layer was an acrylic glass plate, and the other (anisotropic) was a quartz sin gle crystal. In experiments, the elastic waves were generated by a piezoelectric transmitter and received by a piezoelectric transducer contacting the surface of the model medium. The propagation time of a quasi lon gitudinal wave was determined using high order statistics. In the general case, the incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Our study, as well as the results of [10], showed that the predicted effect of multiple splitting of quasi longi tudinal and quasi transverse elastic waves at an interface between different media could not be experimentally observed for a number of technical reasons. We believe their analysis will make it possible to formulate the nec essary requirements for the most appropriate materials and improve the experimental technique.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Our study, as well as the results of [10], showed that the predicted effect of multiple splitting of quasi longi tudinal and quasi transverse elastic waves at an interface between different media could not be experimentally observed for a number of technical reasons. We believe their analysis will make it possible to formulate the nec essary requirements for the most appropriate materials and improve the experimental technique.…”
Section: Discussionmentioning
confidence: 45%
“…Acrylic glass has a density ρ 1 = 1.19 g/cm 3 and the following Lamé parameters: λ = 4534 ± 136 MPa and μ = 1943 ± 58 MPa [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For anisotropic models of semi-infinite substrates the influence of the properties of border discontinuities on the dispersion curves and surface waves was investigated [1], [2]. The authors of [3] and [4] studied the acoustic effects observed in the elastic wave propagation in layered anisotropic media.…”
Section: Introductionmentioning
confidence: 99%